Application of the Define, Measure, Analyze, Improve, and Control (DMAIC) methodology: in the improvement of the loading logistics process in an ice cream factory (Research, Society and Development, 2025)
A certain company, located in the Municipality of Governador Valadares, in the State of Minas Gerais (MG), has been experiencing a scenario marked by recurring errors in its deliveries, including missing, swapped, or damaged products, which has resulted in rework, increased operational costs, and customer dissatisfaction. In this context, the aim of the article is to propose changes in the loading and product verification logistics process of an ice cream factory in Minas Gerais. To address the problem, the DMAIC methodology (Define, Measure, Analyze, Improve, and Control), widely used in continuous improvement programs, was applied in conjunction with quality tools such as Brainstorming, Cause-and-Effect Diagram, Check Sheet, Pareto Chart, and flowcharts. The actions implemented included the adoption of barcode scanning for real-time verification, the inclusion of a second checker for cross-validation, and the application of rigorous criteria to ensure the physical integrity of packaging (boxes, tubs, and bundles). The results showed an overall reduction of 79% in error occurrences, an increase of nearly 20% in the overall customer satisfaction index, and an estimated annual savings of R$ 32,400.00. In addition to quantitative gains, qualitative benefits were identified, such as improved organization during loading, reduced rework, strengthened customer trust, and enhanced organizational climate. This study demonstrates that even in small and medium-sized companies in the food sector, the structured use of quality management methodologies can generate significant and sustainable results, serving as a reference for application in other logistics processes.